To find out your account balance on-line, you need to have your bank or credit union explain the procedure to you. Different financial institutions have different methods for accessing account information. Usually, you need to establish a login name and a password that only you should know.
Please DO NOT POST YOUR ACCOUNT NUMBER. That … Read more

You want to find

**a/b : B/c : C/a**That is 2/3 : 3/4 : 4/2 This can be "rationalized" by multiplying by 12.**8 : 9 : 24**You can find the number with the next lower unit value and the number with the next higher unit value, then determine which is closer. If they are the same distance, we usually consider the higher one to be "closer."
Your number is bracketed by 529 and 530. The distance from 529 is 0.48. The … Read more

Both of the numbers 5 and 13 can be broken apart in ways that can help you perform this subtraction.
Break apart 5:
13 - 5 = 13 - (3 + 2) = (13 - 3) - 2 = 10 - 2 = 8
13 - 5 = 13 - (10 - 5) … Read more

The trapezoidal rule approximates the integral of the function f(x) on the interval [a, b] as
(trapezoidal rule) (b-a)(f(a)+f(b))/2
Simpson's rule uses a second order interpolation to approximate that integral as
(Simpson's rule) (b-a)(f(a) + 4f((a+b)/2) + f(b))/6
In regions where the first derivative is not substantially constant, Simpson's rule will give better … Read more

Often, a "constant of proportionality" is needed. This could be written as y = k/m^2, where k is some appropriate constant.

9/50 is about 10/50, or 2/10
7/15 is about 7.5/15 = 1/2 or 5/10
An estimate of the sum is (2+5)/10 = 7/10 = 0.7

**The actual sum is (9*3+7*10)/150 = 97/150**97/150 ≈ 0.647, so our estimate was a little high. This is because the numbers we used in our estimate were both higher … Read moreA dictionary definition is "one of two or more numbers, algebraic expressions, or the like, that when multiplied together produce a given product." That is the definition of the noun. Factor can also be a verb, in which case it means "resolve into factors."
For example, we can factor the expression … Read more

(x - 2) = 5/4 (multiply by (x-2)/4)
x = 3 1/4 (add 2)

The answer is in bold text on the first line.

{50, 50}, {50, 25, 25}, {25, 25, 25, 25},
{50, 25, 5, 5, 5, 5, 5}, {50, 5, 5, 5, 5, 5, 5, 5, 5, 5, 5},
{25, 25, 25, 5, 5, 5, 5, 5}, {25, 25, 5, 5, 5, 5, 5, 5, 5, 5, 5, 5},
{25, 5, 5, 5, 5, 5, 5, 5, … Read more

You can finish taking the logarithms and see what falls out. You know that
log(ax^b) = log(a) + b*log(x)
Using this, you can simplify your expression as follows
5log(2x) - log(x) - log(4x^2)
= 5(log(2) + log(x)) - log(x) - (log(4) + 2log(x))
= 5log(2) - log(4) + 5log(x) - log(x) … Read more

A right triangle with hypotenuse 28 cm and one side 13 cm will have the other side of length √(28

^{2}- 13^{2}) = √615 ≈ 24.8 cm. Because the base of the ladder is 9 cm from the ground, the top of the ladder will be**33.8 cm**from the ground.The solution is
y(t) = a*e^t + b*e^(5t)
where "a" and "b" are constants that depend on the values of the initial conditions

**.**b = (y''(0) - y'(0))/20 a = y'(0) - 5bThere are several different ways to write expanded form. One of them just separates the digits:
2.07 = 2 + .07
Another way to write expanded form shows the place value of each digit:
2.07 = 2*1 + 0*0.1 + 7*0.01
Yet another way to write expanded form makes use of exponents to … Read more

Sometimes the numbers work out so you can do the problem without converting to/from improper fractions. 1/6 of the project is complete, so 1 - 1/6 = 5/6 of the project remains to be completed.
(5/6)*(6 3/5) = (5/6)*(6) + (5/6)*(3/5) = 5 + 3/6 =

**5 1/2****5 1/2 miles**of freeway must be … Read moreThe following divisibility rules may be important for the nature of such a problem. For divisibility by 2, the units digit of the number should end in either 0; 2; 4; 6 or 8.For divisibility by 3, the sum of the digits of the number should be divisible by 3.For divisibility by 5, the units … Read more

The last two equations are suitable for elimination.
3(2y+3z) + 2(-3y+2z) = 3(14) + 2(5)
9z + 4z = 42+10
13z = 52
z = 4
Substituting into the second equation
2y + 3(4) = 14
y = (14 - 12)/2 = 1
Substituting into the first equation
… Read more